FACTORS RELATED TO THE EVENT OF SIBLING RIVALRY IN CHILDREN 1-5 YEARS OLD IN LABIBIA SUB-DISTRICT OF MANDONGA DISTRICT IN KENDARI CITY: Sibling Rivalry - Islaeli, Islaeli; Purnama Sari, Anisa (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2020)
Background: Child psychological development is an important part of child welfare indicators. The development of child psychology determines the mental readiness of children, one of the problems in children's psychological development is sibling rivalry, which is a sense of competition due to the birth of a younger sibling, causing competition to get attention from their parents. Based on the initial survey, out of 8 mothers with children aged 1-5 years said that since the arrival of their new siblings, their first children often fuss and cry for no reason and want to always be noticed, sometimes even want to hit and injure their younger siblings. This study aims to determine the factors associated with the incidence of sibling rivalry in children aged 1-5 years in Labibia village, Mandonga sub-district, Kendari city. Methods: The type of study was cross sectional design method. The sample in this study were all mothers who had two or more children aged 1-5 years in Labibia Village, Mandonga District, namely 39 mothers. The sampling technique used simple random sampling, the method of analysis used the Chi Square test. Result: The results of this study, showed that there was a moderate relationship between knowledge and the incidence of sibling rivalry (X2 count = 6.955> the value of X2 table = 2.705) and the value of phi (?) = 0.422, there was a moderate relationship between parenting styles and the incidence of sibling rivalry (X2 Count = 8,269> the value of X2 Table = 2.705) and the value of phi (?) = 0.460 and there is a strong relationship between attitude and the incidence of sibling rivalry (X2 count = 18.373> value of X2 Table = 2.705) and the value of phi (?) = 0.686. Conclusion: It is hoped that the parents further increase knowledge and awareness of the behaviors given and understanding of good parenting, with a good attitude will have a positive impact on their children.